Update on NKCC2 regulation in the thick ascending limb (TAL) by membrane trafficking, phosphorylation, and protein-protein interactions - Maskey, Dipak; Granados Pineda, Jessica; Ortiz, Pablo A. (Frontiers in Physiology, 2024)
Purpose of reviewThe thick ascending limb (TAL) of loop of Henle is essential for NaCl, calcium and magnesium homeostasis, pH balance and for urine concentration. NKCC2 is the main transporter for NaCl reabsorption in the TAL and its regulation is very complex. There have been recent advancements toward understanding how NKCC2 is regulated by protein trafficking, protein-protein interaction, and phosphorylation/dephosphorylation. Here, we update the latest molecular mechanisms and players that control NKCC2 function, which gives an increasingly complex picture of NKKC2 regulation in the apical membrane of the TAL.Recent FindingsProtein-protein interactions are required as a regulatory mechanism in many cellular processes. A handful of proteins have been recently identified as an interacting partner of NKCC2, which play major roles in regulating NKCC2 trafficking and activity. New players in NKCC2 internalization and trafficking have been identified. NKCC2 activity is also regulated by kinases and phosphatases, and there have been developments in that area as well.SummaryHere we review the current understanding of apical trafficking of NKCC2 in the thick ascending limb (TAL) which is tightly controlled by protein-protein interactions, protein turnover and by phosphorylation and dephosphorylation. We discuss new proteins and processes that regulate NKCC2 that have physiological and pathological significance.